Listening Comprehension and Written Comprehension: How to Solidify Their Links While Maintaining Their Specificities? - Allen, Nancy (Swiss Journal of Educational Research, 2017)
The links between listening and reading comprehension are undeniable, although distinct characteristics are imputed to them. In this article, we intend to describe qualitatively the metacognitive strategies verbalized by six pupils of sixth grade (11-12 years) of Quebec elementary school in a listening project. In the latter, they used a grid to account for their listening comprehension. Their verbalizations tell us that they essentially use a note-taking strategy to retain information. This data helps us to think about the use of this strategy in a transdisciplinary perspective of education.